Proses Fisioterapi dan Peningkatan Pengetahuan tentang Fisioterapi pada Lansia di Raya - Fujastawan, I Ngurah Gede Verar; Ginting, Isaharpika Br; Herawati, Noni; Damanik, Rodearni (Jurnal Riset Hesti Medan, 2024)
One of the vital components in human life is health, if a person's health is disturbed then the person's survival will not go well (Apta, 2011). Especially parents who naturally experience physical and psychological decline. Complaints appear along with these setbacks, such as joint and bone disorders which result in a decrease in the ability to carry out daily activities independently (Collins et al., 2019). This community service activity is carried out as an effort to introduce the science of physiotherapy to the general public through community service activities. counseling and free physiotherapy treatment aimed at parents and the elderly in Gunung Karang Village, Bobotsari District, Purbalingga Regency. This community service activity was held on December 11, 2022, attended by 78 participants. The counseling material includes an understanding of physiotherapy, an introduction to the types of physiotherapy services, and cases handled by physiotherapy. Prior to the extension activities, the participants first answered the questions contained in the pre-test questionnaire to determine the participants' level of knowledge of the material to be delivered. And as an evaluation material, an assessment of the participants' knowledge was also carried out after the counseling was carried out through a post-test questionnaire. Based on the results of the analysis above, there is a significant.